ESP for economy and business: A critical needs analysis of English language teaching in today's market economy in Algeria - Salima Maouche (International Journal of Education and Learning, 2021)
Some decades ago, Algeria began a transformation from a planned economy to a market economy, for which English became a requirement. The Algerian government believes that promoting English language learning is an attempt to become competitive globally. This emphasis on English resulted in various curricular reforms, influenced by the economic globalization, as the nation attempted to shape its educational systems to provide the skills for a growing global economy. Through this contribution, we believe that contributors have to rethink the role of English in education, employment, social status, and financial development. Moreover, in pedagogy, it is better to shift from ESP to teaching TEGCOM (Teaching English for Globalized Communication), allowing interaction between global forces in specific socio-cultural contexts. Therefore, in working together, the Algerian contributors can prove their English ownership and exercise their agency in their different market creative practices.